Interaction Analysis of Thin Film Composite Membrane Using Trimesoyl Chloride - Piperazine by Dynamic Molecular - Wan Zulaisa Amira, Wan Jusoh; Sunarti, Abd Rahman; Abdul Latif, Ahmad; Nadzirah, Mohd Mokhtar (Universiti Malaysia Pahang, 2018)
Polyamide thin film composite (TFC) membranes are very favourable particularly in pervaporation dehydration and reverse osmosis field for their performance and strength. TFC is produced using interfacial polymerization (IP) technique between aqueous and organic monomer. However, the interaction between monomers is not well discussed at the atomic level and likelihood to produce a loose TFC membrane. Thus, this paper aims to analysis the interaction between aqueous monomer - organic monomer using Molecular Dynamic (MD) simulation to form TFC membrane. This work was done by the Piperazine (PIP), aqueous monomer with the organic monomer, Trimesoyl Chloride (TMC) in the binary systems. The simulation involved the setting of Ewald Summation Method, COMPASS force field, equilibrium phase by microcanonical, NVE (constant volumes and total energy) and run-production stage by NPT (constant pressure and temperature). Analysis by the Radial distribution function (RDF) explicates the intermolecular interfacial of 5.75 Å between the bonding of N (Amine) - C (TMC) atoms at the distance 1.0 Å. This study suggested that the TFC formed by the interaction between TMC - PIP is stable based on interaction higher interaction at very short distance.